The whispering room ebook - Koontz, Dean (Jane Hawk, 2017)
NEW YORK TIMES BESTSELLER • Jane Hawk—fiction’s most relentless, resourceful, stunning new heroine—continues her battle against a murderous conspiracy in the riveting sequel to The Silent Corner. “No time to delay. Do what you were born to do. Fame will be yours when you do this.” These are the words that ring in the mind of mild-mannered, beloved schoolteacher Cora Gundersun—just before she takes her own life, and many others’, in a shocking act of carnage. When the disturbing contents of her secret journal are discovered, it seems certain that she must have been insane. But Jane Hawk knows better. In the wake of her husband’s inexplicable suicide—and the equally mysterious deaths of scores of other exemplary individuals—Jane picks up the trail of a secret cabal of powerful players who think themselves above the law and beyond punishment. But the ruthless people bent on hijacking America’s future for their own monstrous ends never banked on a highly trained FBI agent willing to go rogue—and become the nation’s most wanted fugitive—in order to derail their insidious plans to gain absolute power with a terrifying technological breakthrough. Driven by love for her lost husband and by fear for the five-year-old son she has sent into hiding, Jane Hawk has become an unstoppable predator. Those she is hunting will have nowhere to run when her shadow falls across them. Don’t miss any of Dean Koontz’s gripping Jane Hawk thrillers: THE SILENT CORNER • THE WHISPERING ROOM • THE CROOKED STAIRCASE • THE FORBIDDEN DOOR  • THE NIGHT WINDOW  Praise for The Whispering Room “Koontz has never exactly shied away from complex characters or situations. And this situation gets very complex indeed, as Jane pursues the people behind the conspiracy with the kind of single-minded relentlessness that makes the book absolutely spellbinding. As good as The Silent Corner was, this one’s even better. . . . Koontz is on another roll with a new series that boasts a juicy premise and a compelling star. . . . Pure gold.” — Booklist (starred review)   “A deeply layered, satisfying thriller that is character-driven and nearly impossible to put down . . . grounded in many real-world, current issues . . . [ The Whispering Room ] never loses sight of the classic political/sci-fi/thriller elements that make it so much fun to read.” —Bookreporter